Céline: The Authorized Biography - Germain, Georges-Hébert (Dundurn Press, 1998)
Simply entitled Céline, this is the long-awaited, authorized biography of Céline Dion, the rags-to-riches story of a woman who has become the leading recording artist in the world. First published in French in Quebec in December 1997, Céline has sold in excess of 120,000 copies in Quebec alone. A French-language edition will be released in France this fall, to coincide with the release of a new French album.